Enterprise resource planning, entrepreneurial orientation, and the performance of SMEs in a South Asian economy: The mediating role of organizational excellence - Rabeeya Raoof; Muhammad Farhan Basheer; Shabbir Javeria; Saira Ghulam Hassan; Sadia Jabeen (Cogent Business & Management, 2021)
The key objective of the current study is to examine the effect of enterprise resource planning and entrepreneurial orientation on organizational performance. In addition to that, the study also examines the mediating role of organizational excellence in the relationship between enterprise resource planning and entrepreneurial orientation and OP. The data was collected from the managers of manufacturing SMEs in Pakistan. We distributed 340 questionnaires to the selected respondents, out of which 260 were returned indicating a response rate 76.47%. The SEMP-LS was used for the data analysis. The relationship between them is interrelated where one leads to the other. In this study, the relationship between organizational excellence and organizational performance was found to be positive and significant. In addition, the result showed that organizational excellence is a partial mediator in this relationship according to the value of Variance. The relationship between enterprise resource planning, as a composite construct, and the OP was found to be positive and significant at a 0.01 level of significance; therefore, the hypothesis is supported. The study will be helpful for policy makers, enterprises owners, students, and researchers in understanding the issues related to enterprise resource planning, organizational excellence, entrepreneurial orientation and organizational performance of SMEs operating in Pakistan.
Keywords: 650; enterprise resource planning; Entrepreneurial Orientation; organizational excellence; SME; Pakistan